Capturing the worlds of multiple sclerosis: Hannah Laycock's photography. Issue 1 (31st October 2016) - Bolaki, Stella
Abstract : This essay explores UK photographer Hannah Laycock's Awakenings and, to a lesser extent, Perceiving Identity that were created in 2015, following her diagnosis with multiple sclerosis (MS) in 2013. It draws on scholarship by people with chronic illness while situating these two MS projects in the context of Laycock's earlier art and portrait photography dealing with fragility, image and desire, and power relations between subject and observer. The analysis illustrates how her evocative photography captures the lived or subjective experience of an invisible and often misunderstood condition by initially focusing on the tension between transparency and opacity in her work. It further shows how her images counter dominant didactic metaphors such as, 'the body as machine', that perpetuate the dehumanising and objectifying aspects of medical care. Subsequent sections trace the influence that Oliver Sacks has had on Laycock's practice, and reflect on other metaphors and tropes in Awakenings that illuminate the relationship between body and self in MS. The essay concludes by acknowledging the therapeutic power of art and calling upon health professionals to make more use of such artistic work in clinical practice.